1988
DOI: 10.1021/bi00405a045
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific .epsilon.-amino monoacylation of pancreatic phospholipase A2. 1. Preparation and properties

Abstract: The lipid-binding domain of pancreatic phospholipases A2 contains a number of exposed, hydrophobic amino acid side chains that are involved in the binding of the enzyme to organized lipid-water interfaces. Besides these apolar residues, at least two positively charged lysine groups are present in positions 10 and 116 of the lipid-binding domain. In order to investigate the possible function of these basic side chains in the lipid-binding process, a number of specifically acylated enzyme mutants were prepared, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…The functional consequence of this event was the conversion of the inactive phospholipase A2 monomer to a catalytically effective enzyme dimer that exhibited enhanced interaction with phospholipid monolayers. Similarly, chemical acyhtion with a series of fatty acids of lysyl 6-NH2 groups in pancreatic phospholipase A2 converted the soluble enzyme into a membrane-penetrating form (20). These studies also demonstrated that attachment of acyl groups to hydrophobic regions, as opposed to hydrophilic regions, significantly enhanced the degree of membrane penercation, and that this penetration was optimized by utilizing fatty acids with smaller molecular areas.…”
Section: Time (Rain)mentioning
confidence: 87%
“…The functional consequence of this event was the conversion of the inactive phospholipase A2 monomer to a catalytically effective enzyme dimer that exhibited enhanced interaction with phospholipid monolayers. Similarly, chemical acyhtion with a series of fatty acids of lysyl 6-NH2 groups in pancreatic phospholipase A2 converted the soluble enzyme into a membrane-penetrating form (20). These studies also demonstrated that attachment of acyl groups to hydrophobic regions, as opposed to hydrophilic regions, significantly enhanced the degree of membrane penercation, and that this penetration was optimized by utilizing fatty acids with smaller molecular areas.…”
Section: Time (Rain)mentioning
confidence: 87%
“…It may be speculated that the amino group in the side chain of Lys4 in gastric lipase, which in rabbit is the N-terminus, may have a similar role. Alternatively, as has been proposed for phospholipases A2, the lysine residues within the binding surface could be directly involved in substrate binding by interacting with negative charges on the substrate surface [21]. Such a function for Lys4 in human gastric lipase cannot be ruled out.…”
Section: Discussionmentioning
confidence: 98%
“…The amino acid residues that constitute the postulated binding surface are located along the entire peptide chain [21]. Although most residues of the lipid-binding surface have hydrophobic side chains, a few positively charged lysine residues are present [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] proposed that the interfacial binding face has a cluster of amino acid residues located at one side of the protein. Biochemical studies of PLA 2 s from various sources have indicated that Leu2 [7,8], Trp3 [7–9], Arg6 [7,8,10,11], Lys10 [12–14], Met20 [7,15], Leu31 [7,16], Lys56 [14,17,18], Leu64 [19], Val65 [19], Asn67 [19] and Lys116 [12–14] in the porcine enzyme are involved in its binding to aggregated phospholipids.…”
mentioning
confidence: 99%